A semi‐commercial case study of willow biomass production in the northeastern United States. (9th March 2021) - Montes, Felipe; Fabio, Eric S.; Smart, Lawrence B.; Richard, Tom L.; Añó, Rodrigo Masip; Kemanian, Armen R.
Abstract: Shrub willow ( Salix spp. and hybrids) is a biomass crop well adapted to the northeastern United States. We assessed the biomass productivity of six willow cultivars in a 14.5‐ha field in Pennsylvania through two rotation cycles of 3 yr each, comparing the realized and biophysical yield potential. We also evaluated the relationship of yield with plant density and the harvest efficiency. The realized yield of the best cultivars was about 8 Mg ha –1 yr –1, well below the calculated harvestable potential of 14 Mg ha –1 yr –1 . Uniform stands of willow without planting gaps may maximize yield with 8 × 10 3 plants ha –1, but upright cultivars may benefit from higher densities. Harvest is relatively slow at 1 ha h –1 or 20 Mg h –1 in the longest rows with optimal ground conditions, which makes the harvest cost per hour high. Biotic stresses built up gradually during the 7 yr of the experiment affecting two cultivars severely. The cultivar S . miyabeana × S . viminalis 'Preble' was defoliated by a growing population of willow leaf beetle ( Plagiodera versicolora ), whereas the cultivar S . purpurea 'Fish Creek' was affected by two fungal diseases and suffered a major stand loss in the winter of 2019/2020. Both examples justify breeding for insects and diseases resistance. The moderate harvestable yield and high harvest cost imply that in the northeastern United States, the viability of willow for bioenergy with carbon capture and storage as a tool to reduce CO2 emissions may depend on the provision and monetization of additional ecosystem services. Core Ideas: Shrub willow commercial yields are <8 Mg ha −1 yr −1 or ≈ 67% of the yield potential. Pests and diseases can lower yields or wipe out elite cultivars, justifying breeding. Current operational harvest efficiency is a bottleneck of the system. Current technologies favor ecosystem services provision with biomass as co‐product.